A comprehensive analysis of the hub genes for oxidative stress in ischemic stroke - Zhou, Qing; Dong, Yang; Wang, Kun; Wang, Ziyan; Ma, Bingquan; Yang, Bo (Frontiers in Neuroscience, 2023)
Abstract: Ischemic stroke (IS), induced by the blood flow blockade mediated by cerebral artery occlusion, is a harmful threaten to public health due to high morbidity and mortality. Oxidative stress (OS) has been confirmed to be engaged in the IS pathological process and neural death. Deciphering the essential role of OS-related genes in ischemic stroke may improvise the current perception of the pathophysiological process in IS. Herein, by integrating three IS datasets (GSE16561, GSE22255, and GSE58294), we divided IS samples into low and high OS groups by calculating the OS score identified by the oxidative stress gene set. The functional enrichment analysis of differentially expressed genes (DEGs) between low and high OS groups indicated that DEGs were associated with hypoxia, inflammation response, and oxidative phosphorylation pathways. Furthermore, 9 hub genes (namely TLR1, CXCL1, MMP9, TLR4, IL1R2, EGR1, FOS, CXCL10, and DUSP1) were identified through the Gievan-Newman algorithm and cytohubb algorithms. 9 hub genes were highly expressed in IS samples and they were positively related to neutrophils and macrophages. Drug-sensitive analysis targeting hub genes defined allopurinol and nickel sulfate as potential candidates for impairing the neural death caused by oxidative stress in IS. Finally, we employed five machine learning methods to check the efficacy of the prognostic model identified by 9 hub genes. Results showed that our prognostic signature had superior power in predicting the OS activity of IS patients. TLR4 was found to carry excellent diagnostic value and had a wide-spectrum interaction with other hub genes. Our research emphasized the impacting degree of oxidative stress on ischemic stroke, which supports the idea that antioxidants hold great promise in ischemic stroke therapy.